Smoke and Mirrors: The Perceived Benefits of Continued Tobacco use Among Current Smokers - Klein, Hugh (Health Psychol Res, 2014)
Despite 50+ years of public health efforts to reduce smoking rates in the United States, approximately one-fifth of the adults living in this country continue to smoke cigarettes. Previous studies have examined smokers’ risk perceptions of cigarette smoking, as well as the perceived benefits of quitting smoking. Less research has focused on the perceived benefits of smoking among current cigarette smokers. The latter is the main focus of the present paper. Questionnaire-based interviews were conducted with a community-based sample of 485 adult current cigarette smokers recruited from the Atlanta, Georgia, metropolitan area between 2004 and 2007. Active and passive recruiting approaches were used, along with a targeted sampling strategy. Results revealed that most current cigarette smokers perceive themselves to experience benefits as a result of their cigarette use, including (among others) increased relaxation, diminished nervousness in social situations, enjoyment of the taste of cigarettes when smoking, and greater enjoyment of parties when smoking. Perceiving benefits from cigarette smoking was associated with a variety of tobacco use measures, such as smoking more cigarettes, an increased likelihood of chain smoking, and overall negative attitude toward quitting smoking, among others. Several factors were associated with the extent to which smokers perceived themselves to benefit from their tobacco use, including education attainment, the age of first purchasing cigarettes, the proportion of friends who smoked, hiding smoking from others, being internally-oriented regarding locus of control, and self-esteem.